Drill design using the `control-chaos continuum`: Blending science and art during return to sport following knee injury in elite football - Allen, T.; Wilson, S.; Cohen, D. D.; Taberner, M. (Physical Therapy in Sport, 2021)
Establishing the level of risk, planning and adapting the return to sport (RTS) process following a complex knee injury involves drawing on a combination of relevant high-quality evidence and practitioner experience. On-pitch rehabilitation is a critical element of this process, providing an effective transition from rehabilitation to team training. The `control-chaos continuum` (CCC) is an adaptable framework for on-pitch rehabilitation moving from high control to high chaos, progressively increasing running load demands and incorporating greater perceptual and neurocognitive challenges within sport-specific drills. Drills are a key element of the CCC, and are designed to ensure specificity, ecological validity and maintaining player interest. We showcase drill progression through the phases of the CCC, highlighting the use of constraints to create drills that incorporate the physical, technical, tactical and injury-specific needs of the player. We also provide recommendations to help practitioners create training session content using the CCC to help replicate the demands of team training within their own environment.